2021
DOI: 10.22146/jtbb.60805
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of Mycorrhiza for Seed Germination and Growth of <i>Dendrobium</i> Orchids

Abstract: Indonesia is a tropical country that has natural forests and is suitable for orchid species habitat, leading to more than 5,000 species of orchids grow. The tropical area is the main distribution centre for epiphytic orchids, one of which is Dendrobium, which grows more than 1,000 species throughout the world. Orchid seeds are very small and do not have an endosperm, making germination difficult in their natural habitat. Mycorrhizal association with orchids plays a role in the survival of orchids in nature thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…increased nutrient intake in plants and increased seed germination on Dendrobium nobile and Dendrobium chrysanthum . 16 Epulorhiza repens ML01 can successfully establish and survive in pot orchids under greenhouse conditions, and reduce the occurrence of diseases in the Cymbidium hybridum roots. 59 This study demonstrated the promoting effect of Epulorhiza sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…increased nutrient intake in plants and increased seed germination on Dendrobium nobile and Dendrobium chrysanthum . 16 Epulorhiza repens ML01 can successfully establish and survive in pot orchids under greenhouse conditions, and reduce the occurrence of diseases in the Cymbidium hybridum roots. 59 This study demonstrated the promoting effect of Epulorhiza sp.…”
Section: Discussionmentioning
confidence: 99%
“…Orchidaceae is a species-rich and diverse family of flowering plants comprising approximately 28,000 species in 880 genera. 15 , 16 Paphiopedilum Pfitzer are famous worldwide because of their unique flower shape, attractive colors, and long flower lifespan. They are also known as slipper orchids; they have a high ornamental value and are one of the most popular genera of family Orchidaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satunya adalah jenis anggrek yang tersebar di seluruh hutan hujan tropis. Seperenam jenis anggrek di dunia dapat ditemukan di Indonesia (Semiarti et al, 2020). Jumlah spesies anggrek didunia yaitu sekitar 5.000 spesies dari total sekitar 30.000 spesies terdapat di Indonesia (Clarissa & Halim, 2019).…”
Section: Pendahuluanunclassified
“…Peluang anggrek untuk dibudidayakan akan meningkatkan pendapatan masyarakat (Semiarti et al, 2020). Mulai dari bunga anggrek yang mudah dibudidayakan hingga anggrek yang tergolong langka, menjadi faktor yang menarik perhatian masyarakat untuk membudidayakannya atau sekedar menjalankan hobi (Clarissa & Halim, 2019).…”
Section: Pendahuluanunclassified
“…Spesies ini memiliki cara hidup terestrik yang identik bersimbiosis dengan mikoriza untuk keberlangsungan hidupnya. Mikoriza berperan dalam suplai nutrien bagi anggrek, dan anggrek memberikan produk karbon kepada mikoriza sebagai nutrisi (Garcia & Zimmerman, 2014;Tsulsiyah et al, 2021). Thelymitra javanica pada penelitian ini hanya dijumpai mulai ketinggian 2.563 mdpl dan tumbuh optimal mulai ketinggian 3.000 mdpl sehingga aman dari ancaman dan gangguan aktivitas manusia.…”
Section: Pembahasanunclassified